Innovating the Personalization of Stratified Survivorship Care Pathways: Using a Cancer Data Ecosystem to Improve Care Access, Outcomes, Efficiency, and Costs. Issue 57 (3rd September 2021) - Alfano, Catherine M; Suarez-Almazor, Maria; Rodriguez, Maria Alma; Palos, Guadalupe R; Gilmore, Katherine R
Abstract: New models of survivorship care are needed that improve outcomes for the growing number of cancer survivors, address the increasing complexity of their health needs, and deal with the shortage of clinicians and rising costs of this care. Technology can aid the delivery of personalized, stratified survivorship care pathways where the intensity of care, the care setting, and the providers required for that care vary with survivors' needs. Building a cancer data ecosystem of connected data streams that supports and learns from each patient can be used to streamline care, enhance efficiency, reduce costs, and facilitate research. This manuscript describes the input, analytics, and output components of the cancer data ecosystem that must be built and connected and also provides a real-world use case of how such a system could transform care in a large US comprehensive cancer center.